Behaviour of heat-damaged partially-insulated RC beams using NSM systems. (20th August 2018) - Jadooe, Awad; Al-Mahaidi, Riadh; Abdouka, Kamiran
Highlights: Effect of elevated temperature in RC beams was investigated. NSM CFRP laminate was found to reinstate the strength of RC beams. Cement-based adhesive was utilized as an effective bonding agent. The FEM models were able to predict the experimental findings. Abstract: This research shows the results of an experimental and numerical study on the behaviour of RC beams damaged by heating and then strengthened using NSM CFRP laminate and cement-based adhesive. Two beams were left as reference beams and the other beams were heated under the ISO-834 standard fire curve. The experimental variables consisted of unheated and heat-damaged beams, level of heat exposure and use of insulation. The flexural behaviour was investigated after exposure to 700 °C with and without insulation on the top surface of the concrete and after exposure to 800 °C using partial insulation on the top surface of the concrete for two hours. The test results prove the effectiveness of NSM technique in improving the flexural strength, stiffness, and ductility after repairing the RC beams with NSM system compared with unheated and heat-damaged beams. Moreover, finite element models (FEMs) were found to be able to predict the behaviour of undamaged and heat-damaged RC beams reasonably well.